Acute effects of tea constituents L‐theanine, caffeine, and epigallocatechin gallate on cognitive function and mood: a systematic review and meta‐analysis. (19th June 2014) - Camfield, David A; Stough, Con; Farrimond, Jonathon; Scholey, Andrew B
<x xml:space="preserve">Abstract</x> A systematic review and meta‐analysis was conducted on 11 randomized placebo‐controlled human studies of acute effects of tea constituents L‐theanine and epigallocatechin gallate, administered alone or in combination with caffeine, on cognitive function and mood. The outcome measures of mood were alertness, calmness, and contentedness, derived from the Bond‐Lader scales, and state anxiety, from the State‐Trait Anxiety Inventory. Cognitive measures assessed were attentional switch, intersensory attention, and rapid visual information processing. Standardized mean differences between placebo and treatment groups are presented for each study and outcome measure. Meta‐analysis using a random‐effects model was conducted when data were available for three or more studies. Evidence of moderate effect sizes in favor of combined caffeine and L‐theanine in the first 2 hours postdose were found for outcome measures Bond‐Lader alertness, attentional switching accuracy, and, to a lesser extent, some unisensory and multisensory attentional outcomes. Moderator analysis of caffeine and L‐theanine doses revealed trends toward greater change in effect size for caffeine dose than for L‐theanine dose, particularly during the first hour postdose.